Does Shari’ah screening methodology matter? - Jamil, Nor Suhaira; Hassan, Hamizah; Samsudin, Syamsyul; Mustafa, Nik Nur Shafika; Haris, Balkis (International Journal of Engineering and Technology, 2018)
The identification of Shari’ah compliant stocks is known as Shari’ah screening, which is announced to the public twice a year. The previous methodology is employed in 1995 to May 2013 and the revised methodology is employed in November 2013 until now, which provides certainty and clarity on the status of stocks listed on the stock exchange. There is a lack of research conducted to study the effect of classifying stocks as Shari’ah compliant and non-Shari’ah compliant on stock returns, by employing both previous and revised methodologies at a time. Hence, this study aims to investigate the effects of announcement of inclusion (removal) of stocks in (from) the Shari’ah Compliant List on stock returns, using the previous and revised Shari’ah screening methodology. Employing the event study methodology in years 2007 – 2015, this study found that inclusion of stocks in Shari’ah Compliant List leads to the increment of stock returns, whilst the removal of stocks from the list leads to the decreasing of stock returns regardless of using the previous or revised screening methodology.